2021
DOI: 10.1016/j.agwat.2021.107031
|View full text |Cite
|
Sign up to set email alerts
|

A model for estimating Ag-MAR flooding duration based on crop tolerance, root depth, and soil texture data

Abstract: Agricultural Managed Aquifer Recharge (Ag-MAR) is an emerging MAR technique that uses agricultural fields as percolation basins to recharge the underlying aquifers. Ag-MAR can be a beneficial solution for storing excess surface water, however, if not managed properly it can potentially harm the soil and crops planted on the field at the time of recharge, ultimately leading to yield loss. Root zone residence time (RZRT), defined as the duration that the root-zone can remain saturated (or nearly saturated) durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…However, flooding fields for long periods of time might negatively impact crop performance, as shown for V1, which needs to be considered and balanced (Levintal et al, 2022). A possible solution is to use a new model that predicts crop damage as a function of the duration of saturated conditions in the soil root-zone, soil texture, and crop tolerance to waterlogged conditions (Ganot and Dahlke, 2021a).…”
Section: Quasi Steady Flooding Stagementioning
confidence: 99%
See 1 more Smart Citation
“…However, flooding fields for long periods of time might negatively impact crop performance, as shown for V1, which needs to be considered and balanced (Levintal et al, 2022). A possible solution is to use a new model that predicts crop damage as a function of the duration of saturated conditions in the soil root-zone, soil texture, and crop tolerance to waterlogged conditions (Ganot and Dahlke, 2021a).…”
Section: Quasi Steady Flooding Stagementioning
confidence: 99%
“…In California, for example, Ag-MAR is implemented as one of the methods to overcome ongoing groundwater depletion (Kocis and Dahlke, 2017). However, using farmland as spreading grounds bears the risk to leach contaminants from the water or soil to groundwater which can impact drinking water quality (Bachand et al, 2014), waterlogging of the root zone for long periods that can reduce crop health (Ganot and Dahlke, 2021a), and ecosystem service tradeoffs, such as short and long-term effects on in-stream flows (Levintal et al, 2022). Out of the above, leaching of legacy nitrogen (N), mainly in the form of nitrate (NO 3 -), is possibly the most widespread environmental risk of Ag-MAR.…”
Section: Introductionmentioning
confidence: 99%
“…Crop models represent the mathematics of agricultural processes based on theory and empirical research; thus, the representation entails different assumptions and simpli cations of reality that make the output variables uncertain and inaccurate (Han et al, 2019;Andrea Saltelli et al, 2008). On the other hand, too many parameters (up to hundreds) must be speci ed to describe the properties of the soil-crop-atmosphere system (Ganot & Dahlke, 2021;Thorp et al, 2020). Estimating every parameter in the model needs signi cant eld measurements, which is costly and time-consuming.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Zaidi et al (2015) identified suitable MAR locations in Saudi Arabia by overlaying maps of soil texture, vadose zone thickness, land use, and slope. A common alternative approach to these MCDA analyses conducted in Geographic Information Systems is the identification of MAR locations and their benefits and risks through numerical modeling (Bachtouli & Comte, 2019;Ganot & Dahlke, 2021;Kacimov et al, 2016;Tzoraki et al, 2018;Wurl & Imaz-Lamadrid, 2018;Zlotnik et al, 2017). Scherberg et al (2014), for example, used the Integrated Water Flow Model (IWFM) (Dogrul, 2013) to quantify the impact of selected MAR scenarios in the Walla River basin, USA.…”
mentioning
confidence: 99%